Optimization of thermal recovery strategies for offshore heavy oil reservoirs in Bohai Bay, China. (17th January 2016) - Zhang, Yanyu; Chen, Huijuan; Sun, Xiaofei; Duan, Xuewei; Hu, Wentao; Zhang, Xiansong
ABSTRACT: A series of experiments were conducted to test thermal conductivity, heavy oil-water, and heavy oil-steam relative permeabilities used in thermal simulations. The effects on these parameters of temperature, pressure and heavy oil viscosity were also studied. Reservoir simulations were conducted to optimize thermal recovery processes for three heavy oil reservoirs with a range of in situ oil viscosities from 342 to 926 mPa·sec by comparing different operating strategies. The results show that multicomponent thermal fluid flooding achieved better performance for lower viscosity heavy oil. However, steam flooding was found to be more effective for intermediate and higher viscosity heavy oil.